Development of a pregnant woman phantom using polygonal mesh, for dosimetric evaluations - Manuela Ohana Monteiro Cabral; José Wilson Vieira; Viriato Leal Neto; Fernando Roberto de Andrade Lima (Brazilian Journal of Radiation Sciences)
Due to the embryo/fetus radiosensitivity the accurate estimation of the absorbed dose distribution in the abdominal area is an additional problem caused by the exposure of pregnant women to ionizing radiation in medical applications. This paper reports the construction and insertion of a fetal representation in a female geometry by means of 3D modeling techniques. In order to characterize an ECM the Grupo de Dosimetria Numerica (GDN) is using, mainly, simulators emitting gama sources and voxel phantoms coupled to a MC code. The phantoms are predominantly constructed from stacks of magnetic resonance images (MRI), computed tomography (CT) (obtained from scans of real patients) or from 3D modeling techniques. Due to the difficulty of obtaining medical images of pregnant women, 3D objects in several formats (.obj, .max, .blend, etc.) were acquired for anatomical representation of a non-pregnant adult. To construct a fetal representation, the 3D modeling technique called Poly Modeling (polygon mesh) was used inside of the software Autodesk 3ds Max 2014 (free student version). Information about the radiosensibility of organs included in the abdominal area will be used to fit and use the pregnant phantom in numerical dosimetry. For this, the phantom will be voxelized and the masses of organs of interest will be adjusted according to data provided by International Commission on Radiological Protection (ICRP). Finally, the phantom will be coupled to a MC code creating a MCE that will serve as base for the construction of several other models involving pregnant women submitted to ionizing radiation.